Analisis Perilaku Perundungan (Bullying) Siswa Sekolah Menengah Pertama - Tuti Wantu; Idriani Idris (STKIP Andi Matappa, 2022)
The aim of this research is to analyze the bullying behavior that occurs in students of Junior High Schools Negeri in Gorontalo City. The study used a quantitative descriptive research design. The sample consisted of 787 students of state junior high schools in Gorontalo City. The data analysis technique used is descriptive technique using percentage calculation statistics (%). The data collection used was a questionnaire where the weighting of the research questionnaire used a Likert scale that had been tested for validity and reliability. Based on the results of the study, it shows that the bullying behavior of the students of State Junior High Schools in Gorontalo City shows an average of 44.33%, this shows that students of Junior High Schools Negeri in Gorontalo City bullying in the moderate category